The male of Sauris mouliniei (Legrand, 1971) comb. n. (Lepidoptera: Geometridae: Larentiinae: Trichopterygini), an endemic Inner Seychelles moth - Bolotov, Ivan N.; Frolov, Artem A.; Kolosova, Yulia S.; Kondakov, Alexander V. (Zootaxa, 2014)
The history of lepidopteran studies of the Inner Seychelles is about one hundred years old, and the data have been summarized recently in a comprehensive monograph (Gerlach & Matyot 2006). The largest granitic islands contain the greatest number of species—345 for Mahé and 288 for Silhouette—but the second largest, Praslin, has only 42 recorded species. A total of 17 Geometridae species occur in the granitic Seychelles. Among them are six species of Larentiinae with two endemics, including Episteira mouliniei Legrand, 1971, a unique Trichopterygini for these islands (Gerlach & Matyot 2006). This species was described based on a single female specimen in the genus Episteira Warren, 1899. The previously unknown male of the taxon is described herein.